CORRELATION BETWEEN PCAR WITH IPSS SCORE, QMAX, AND POST VOIDING RESIDUAL URINE AND ITS CUT-OFF VALUE IN DETERMINING BOO IN PATIENTS WITH BPH LUTS - Nurhadi, Pradana; Hakim, Lukman; Djojodimedjo, Tarmono; Hardjowijoto, Sunaryo (Indonesian Urological Association, 2017)
Objective: This study was conducted to determine the correlation between Presume Circle Area Ratio (PCAR) and IPSS score, Qmax, and post voiding residual urine (PVR) and to find PCAR cut-off value in determining the presence Bladder Outlet Obstruction (BOO) in Benign prostatic hyperplasia (BPH) Lower Urinary Tract Symptoms (LUTS). Materials & Methods: This study was observational analytic study with 30 BPH LUTS patients as subjects during the period September 2015 to January 2016. The determined variables were PCAR, IPSS score, Qmax, post voiding residual urine (PVR) and analyzed using the SPSS program v21. Results: There were 30 patients who met the inclusion and exclusion criteria with the mean age of 67.47 years. In the correlation test, there was insignificant correlation between PCAR with IPSS (r=0.138, p=0.467), a significant correlation between PCAR with Qmax (r=0.468, p=0.009), PCAR with PVR (r=0.399, p=0.029), PCAR with BOO (r=0.491, p=0.006) PCAR cutoff value is 0.65 with sensitivity of 69% and specificity of 71%. Conclusion: PCAR has a significant correlation with PVR, Qmax and BOO but no significant with IPSS score. PCAR value >0.65 indicating BOO in BPH LUTS. PCAR can be used as an alternative non-invasive examination in determining the existence of BOO.